Jalan Qur’ani dalam Membangun Ketahanan Keluarga dan Kohesi Nasional - Nanda Riswanda Pohan; Zuniar; Murliana; Jurmianti; Tasya Salsabilla (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2026)
This study examines the husband–wife relationship in the Qur’an and its implications for family resilience and national stability. By employing a thematic tafsir (maudhū‘ī) approach, this study analyzes the main principles of the Qur’an that regulate marital relationships, namely mawaddah wa raḥmah (love and affection), ta‘āwun (mutual assistance), mu‘āsharah bil ma‘rūf (ethical and civilized interaction), and qiwāmah (responsible leadership based on justice). This study seeks to respond to contemporary challenges such as the increasing rate of divorce, domestic violence, economic vulnerability, and the emergence of the phenomenon of voluntarily choosing not to have children (childfree), all of which indicate the weakening of family structures. Through a qualitative descriptive methodology with a literature review, this paper arrives at the conclusion that there are four frameworks of Qur’anic family transformation, namely: iṣlāḥ al-fard (individual reform), iṣlāḥ al-usrah (family reform), iṣlāḥ al-mujtama‘ (societal reform), and iṣlāḥ al-bilād (state reform). This framework positions the family as a strategic core in sustainable nation-building. This study contributes to Qur’anic studies, Islamic family law, and the discourse on social resilience by offering an integrative model that connects spiritual reform with socio-political stability.